Identifikasi prekursor tanah longsor berdasarkan perubahan nilai tahanan jenis batuan menggunakan metode geolistrik time-lapse konfigurasi dipole-dipole di Bukik Lantiak Kecamatan Padang Selatan (Identification of landslide precursors based on changes in the value of rock resistivity using the geoelectric time-lapse method of dipole-dipole configuration in Bukik Lantiak, Padang Selatan District ) - Rifa Kurnia; - Akmam; - Mahrizal (PILLAR OF PHYSICS, 2018)
Landslides are a serious hazard for mankind causing fatality and material loss. Losses generated from landslide events can be minimized by investigating early symptoms or precursors of a landslide event. The research is conducted in Bukik Lantiak, South Padang sub-district by using Geolistrik method of time-lapse Dipole-dipole configuration as effort of early symptoms detection or precursor that can cause the occurrence of landslide disaster. The results shows that there is a  change of rock resistivity value in each measurement path. The percentage change of resistivity  are  -12.25% of path 1, -8.73% of path 2, 3.07% of path 3, and -37.42% of path 4. The landslide precursor can be known from change of resistivity value, when measurements are made on each path at two different times so that the measured resistivity will be different. This difference is caused by the absorption of rainwater by the surface which then migrates into the inner layer